Answer:
13 and 23
Step-by-step explanation:
create an equation to solve:
(2x-3) + x = 36
3x - 3 = 36 combine like terms
<u> +3 +3</u><u> </u> add 3 to both sides
<u>3</u>x = <u>39</u>
3 3 divide both sides by 3
x = 13
<u>13 is the first number</u>
the 2nd number is 3 let than twice the first so we create and solve a new equation:
2x - 3 = ?
2(13) = ? substitute 13 from the
smaller number to solve
<u>23 = the 2nd number</u>
20 in because it will over everything
Answer:
3 : (1/2) =![\frac{6}{1} =6](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B1%7D%20%3D6)
Step-by-step explanation:
Divide: 3 : ![\frac{1}{2} =\frac{3}{1} *\frac{2}{1} =\frac{3 * 2}{1*1} =\frac{6}{1} =6](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%3D%5Cfrac%7B3%7D%7B1%7D%20%2A%5Cfrac%7B2%7D%7B1%7D%20%3D%5Cfrac%7B3%20%2A%202%7D%7B1%2A1%7D%20%3D%5Cfrac%7B6%7D%7B1%7D%20%3D6)
Dividing two fractions is the same as multiplying the first fraction by the reciprocal value of the second fraction. The first sub-step is to find the reciprocal (reverse the numerator and denominator, reciprocal of
is
) of the second fraction. Next, multiply the two numerators. Then, multiply the two denominators.
In words - three divided by one half = six.